TNFR2 blockade promotes antitumoral immune response in PDAC by targeting activated Treg and reducing T cell exhaustion - Eliane Piaggio; Allan Thiolat; Anais Debesset; Caroline Pilon; Benoît Laurent Salomon; José Laurent Cohen; Sylvain Baulande; Sylvain Meunier; Orianne Cuelenaere-Bonizec; Wilfrid Richer; Claire Houppe; Matteo Ponzo; et al. (Journal for ImmunoTherapy of Cancer)
Background Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive cancers, highly resistant to standard chemotherapy and immunotherapy. Regulatory T cells (Tregs) expressing tumor necrosis factor α receptor 2 (TNFR2) contribute to immunosuppression in PDAC. Treg infiltration correlates with poor survival and tumor progression in patients with PDAC. We hypothesized that TNFR2 inhibition using a blocking monoclonal antibody (mAb) could shift the Treg-effector T cell balance in PDAC, thus enhancing antitumoral responses.Method To support this hypothesis, we first described TNFR2 expression in a cohort of 24 patients with PDAC from publicly available single-cell analysis data. In orthotopic and immunocompetent mouse models of PDAC, we also described the immune environment of PDAC after immune cell sorting and single-cell analysis. The modifications of the immune environment before and after anti-TNFR2 mAb treatment were evaluated as well as the effect on tumor progression.Results Patients with PDAC exhibited elevated TNFR2 expression in Treg, myeloid cells and endothelial cells and lower level in tumor cells. By flow cytometry and single-cell RNA-seq analysis, we identified two Treg populations in orthotopic mouse models: Resting and activated Tregs. The anti-TNFR2 mAb selectively targeted activated tumor-infiltrating Tregs, reducing T cell exhaustion markers in CD8+ T cells. However, anti-TNFR2 treatment alone had limited efficacy in activating CD8+ T cells and only slightly reduced the tumor growth. The combination of the anti-TNFR2 mAb with agonistic anti-CD40 mAb promoted stronger T cell activation, tumor growth inhibition, and improved survival and immunological memory in PDAC-bearing mice.Conclusion Our data suggest that combining a CD40 agonist with a TNFR2 antagonist represents a promising therapeutic strategy for patients with PDAC.